Reproducibility-optimized detection of differential DNA methylation - Veronika Suni; Fatemeh Seyednasrollah; Bishwa Ghimire; Sini Junttila; Asta Laiho; Laura L Elo (United Kingdom, 2022)
Compared with state-of-the-art methods, ROTS shows competitive sensitivity and specificity in detecting consistently differentially methylated regions.